Measuring bovine γδ T cell function at the site of Mycobacterium bovis infection - Rusk, Rachel Aline (Kansas State University, 2017)
The causative agent of tuberculosis (TB) in cattle is Mycobacterium bovis (M. bovis). γδ T cells are a unique subset of nonconventional T cells that play major roles in both the innate and adaptive arms of the immune system. Bovine γδ T cells have the capacity for multiple immune functions during infection with M. bovis. However, the alternative functions of γδ T cells as well as the responses of γδ T cells in vivo at the site of infection remain unclear. To identify novel functions for γδ T cells in response to M. bovis infections, RNA sequencing and transcriptomics analysis was completed on peripheral blood γδ T cells isolated from virulent M. bovis-infected cattle. Differentially expressed genes were confirmed with real-time PCR. In an attempt to model in vivo cell-to-cell interactions at the site of infection, γδ T cells were also isolated from naïve and M. bovis-infected calves and co-cultured with autologous, BCG-infected, monocyte-derived macrophages. γδ T cell chemokine and cytokine expression was analyzed via ELISA and real-time PCR. The characteristic lesions of bovine tuberculosis are well-organized pulmonary granulomas. To determine the relevance of the RNA-sequencing and in vitro co-culture results to in vivo infection, tissue samples from granulomatous lesions in the lungs and mediastinal lymph nodes of virulent M. bovis-infected cattle were collected 3 months after infection. mRNA transcripts for γδ T cells expression of-- IFN-γ, IL-17, IL-10, IL-22, and CCL2 were microscopically evaluated within the granulomas using an in situ hybridization system, RNAScope (Advanced Cell Diagnostics Inc.). Co-culture experiments and transcriptomics analysis revealed increased expression of chemokines and various cytokines by γδ T cells responding to M. bovis infection. The novel in situ hybridization assay revealed that cytokine expression by γδ T cells varied within the lesions, with significant levels of CCL2 and IFN-γ, and low expression of IL-10, IL-22, and IL-17 in situ at this time-point after infection. Co-culture experiments also revealed that γδ T cells from virulent M. bovis-infected cattle have the capacity to directly impact the viability of M. bovis in vitro. Our results suggest that γδ T cells accumulate within the granulomas, and influence host immunity to M. bovis by secretion of cytokines and chemokines, and direct cytotoxicity, in response to infected macrophages.
Keywords: Gamma delta T cells; Mycobacterium bovis